Эффективные мероприятия по содействию социокультурной адаптации иностранных студентов в Украине - Северин, Надежда Васильевна; Виктор, Ольга Михайловна (Міжнародний гуманітарний університет, 2019)
Статья посвящена изучению проблемы адаптации иностранных студентов к условиям жизни и учёбы в Украине. Цель статьи – выделение мероприятий, которые влияют на успешную социокультурную адаптацию студентов факультета международного образования НТУ "ХПИ". Подчёркнуты некоторые виды работы, способствующие преодолению "культурного шока". Удачное сочетание учебной и внеаудиторной работы позволяет значительно облегчить вхождение иностранцев в украинскую социокультурную среду.

The article deals with the problem of foreign students’ adaptation to the conditions of life and study in Ukraine. The purpose of the article is to distinguish those activities which influence the successful social and cultural adaptation of students studying at the Department of International Education of NTU “KhPI”. The types of work that help overcome “the culture shock” are highlighted. It is shown that a good combination of study work and extracurricular activities make it much easier for foreign students to become a part of the Ukrainian social and cultural environment.
Effective activities facilitating social and cultural adaptation of foreign students in Ukraine
Keywords: культурный шок; куратор; учебная экскурсия; тематический урок-концерт; culture shock; tutor; study tour; thematic lesson-concert